Orthopedic Treatment of Skeletal Class III Malocclusions With Maxillary Deficiency - Erdal Bozkaya; Sema Yüksel; Tuba Tortop; Neslihan Üçüncü; Emine Kaygısız; Deniz Gencer (Turkish journal of orthodontics, 2015)
Objective:The purpose of this study was to compare the treatment effects of a double-plate appliance (DPA) and a double-plate appliance and facemask combination (DPA-FM) in correcting Class III malocclusions.Materials and Methods:The material consisted of lateral cephalometric radiographs of 40 children with skeletal and dental Class III malocclusion. In the first treatment group, 13 patients (mean age: 10 years 3 months) were treated with DPA. In the second treatment group, 15 patients (mean age: 10 years 9 months) were treated with DPA-FM. In the third group, 12 patients (mean age: 10 years 6 months) were observed without treatment for 9 months. Statistical evaluation was made by ANOVA, Duncan, and paired t tests.Results:The increases in SNA and ANB angles were significantly greater in the DPA-FM group than in the DPA group. The proclination of upper incisors (U1/NA) and retroclination of lower incisors (L1/NB) were significantly greater in the DPA group than in the DPA-FM group. The retroclination of lower incisors (L1/NB) in the DPA group showed a significant difference compared with the control group. The increase in ANS-Me length was significantly greater in the DPA-FM group than in the control group.Conclusion:The DPA-FM treatment was more effective in sagittal correction of the maxilla than the DPA treatment. The dental contribution to Class III treatment seemed to be greater in the DPA group, but in this group vertical skeletal changes were more satisfying.